The Potential Effect of Developed Reader Response Strategy-Based Mobile Reading for Students’ Establishing Character and Comprehension Achievement - Inderawati, Rita; Agusta, Okky Leo; Sitinjak, Mgrt. Dinar (Universitas Sebelas Maret, 2018)
Mobile learning is nowadays utilized by educators to meet the students’ mode of learning in this digital era. This current study’s objective is to develop the mobile learning of reading based reader response strategy for comprehension achievement and character establishment of the eleventh grade students of SMAN 4 Lubuklinggau with 29 student. By employing development research with Analysis, Design, Development, Implementation, and Evaluation (ADDIE) research design , reading test material was delivered to determine the potential effect of students. The result of the study were: the developed product for reading material was effective by showing 26 students (89.65%) out of 29 students achieved the minimum mastery criterion (70) and the students’ answers showed students’ moral knowing and moral feeling in relation to the character building. In term of moral knowing, it showed that students comprehension about moral value inside texts. Students were able to put themselves in moral knowing stage of character building. Besides, the students expressed what they felt and what should they do if they should face the condition.